A New 3D Simulation Method for the Construction of Optical Phase Contrast Images of Gold Nanoparticle Clusters in Biological Cells. (1st December 2008) - Tanev, Stoyan; Pond, James; Paddon, Paul; Tuchin, Valery V.
Abstract : A new 3D simulation method based on the finite-difference time domain (FDTD) approach in combination with Fourier optic techniques is applied to the modeling of optical phase contrast microscope (OPCM) imaging of gold nanoparticles (NPs) in singe biological cells. We consider a realistic size 3D cell model at optical immersion conditions, that is, when the refractive index values of the cytoplasm and of the extracellular medium are equal. For the first time, an FDTD-based OPCM model is applied to visualize the presence of a cluster of gold NPs in the cytoplasm at both resonant and nonresonant conditions. The results demonstrate the capability to model OPCM image enhancement by optically controlling the resonant properties of the NPs. Our research study extends the applicability of the FDTD modeling approach into a new biomedical optics research area.